Female Independence in Pride and Prejudice (2005) Movie: A Feminism Theory - Putri Damayanti, Dinda; Setyabudi, Titis (Universitas Negeri Semarang, 2024)
The purpose of this study is to discover how female independence is portrayed in the Pride and Prejudice (2005) movie and examine the effects of this portrayal. This study applies feminist theory and is classified as a literary study. To analyze the data, researchers used qualitative data analysis. The result reveals that Elizabeth Bennet exemplifies various facets of female autonomy, highlighting the interplay between existential freedom and societal constraints. Her assertiveness, seen in rejecting Mr. Collins and seeking genuine connections over financial stability, underscores the positive effects of resisting traditional gender roles and societal expectations. This defiance promotes critical reflection on norms and encourages societal evolution. The narrative emphasizes economic independence, with Elizabeth's pursuit of love rather than financial security enhancing her relationship with Mr. Darcy and contributing to societal well-being. It also explores sexual freedom and the ambiguity of freedom, showcasing the positive impact of her autonomy on her family and society's perception of her unconventional choices. The study suggests that by examining the Pride and Prejudice (2005) movie, readers and other researchers can gain insights into the portrayal of female independence. This research may serve as a foundation for those with different backgrounds or methods, such as psychological or Marxist approaches, to build on and undertake studies from a broader perspective.